Empirical Penman-Monteith equation and artificial intelligence techniques in predicting reference evapotranspiration: A review - Abdullah S.S.; Malek M.A. (Inderscience Publishers, 2023)
Agricultural robots; Evapotranspiration; Neural networks; Water supply; Weather forecasting; Artificial intelligence techniques; Extreme learning machine; Fao penman monteiths; Food and agriculture organizations; Irrigation projects; Penman-Monteith equations; Reference evapotranspiration; Weather parameters; Learning systems; artificial intelligence; artificial neural network; climate conditions; empirical analysis; evapotranspiration; Food and Agricultural Organization; machine learning; Penman-Monteith equation; prediction; United Nations